1991
DOI: 10.1159/000174775
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydrogen Ion on the Changes in Adenosine Production in the Isolated Rat Heart Perfused at a Constant Flow System

Abstract: This study was designed to clarify the relationship between the change in H+ and the nucleoside concentration at a constant coronary flow rate using a Langendorff system. Wistar rat hearts were perfused with Krebs-Henseleit solution (control, pH 7.4) modified to be either acidotic or alkalotic. Coronary perfusion presssure (CPP), left ventricular pressure, and myocardial oxygen consumption were decreased in the acidotic perfusate. On the other hand, these parameters increased in the alkalotic perfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

1999
1999
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
1
1
Order By: Relevance
“…Our data support this earlier observation. In contrast, Ochi et al [17], who used a constant flow system similar to ours, reported that acidosis (pH 7.2) produced a small decrease in CPP, from 93.9 ± 8.5 to 84.8 ± 6.8mmHg. In their report, the precise timing of the decrease in CPP is not stated but the response is clearly different to that seen by us.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Our data support this earlier observation. In contrast, Ochi et al [17], who used a constant flow system similar to ours, reported that acidosis (pH 7.2) produced a small decrease in CPP, from 93.9 ± 8.5 to 84.8 ± 6.8mmHg. In their report, the precise timing of the decrease in CPP is not stated but the response is clearly different to that seen by us.…”
Section: Discussioncontrasting
confidence: 54%
“…In contrast, a more recent study in the rat described an acidosis-induced coronary dilatation [17]. In view of these apparent contradictory reports we have reexamined the effect of acidosis on coronary resistance in the rat heart.…”
Section: Introductionmentioning
confidence: 88%